Aryne Cycloaddition Reactions in the Synthesis of Large Polycyclic Aromatic Compounds. Issue 27 (4th July 2013) - Pérez, Dolores; Peña, Diego; Guitián, Enrique
Abstract: Cycloaddition reactions involving arynes provide privileged strategies for the convergent synthesis of polycyclic compounds containing aromatic rings. This review focuses on the application of aryne chemistry, in particular [4+2] and palladium‐catalysed [2+2+2] cycloaddition reactions, in the synthesis of large polycyclic aromatic hydrocarbons (PAHs) containing five or more fused benzene rings. Many of the polycyclic compounds included in this report display properties of interest in the field of materials science and some can be considered as nano‐sized graphene substructures or nanographenes. Abstract : The cycloaddition of arynes is a powerful tool for the convergent synthesis of polycyclic aromatic compounds (PACs). The controlled synthesis of large PACs is an important challenge due to the interest in these molecules as functional materials and in graphene chemistry. This microreview covers the synthesis of a variety of large PACs, which are of interest in the field of materials science.